The right kind of house - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2006)
Advantages and disadvantages of wooden, brick and mud-brick houses, importance of hygiene, such as clearing away dung.